2018
DOI: 10.12688/wellcomeopenres.14439.2
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations in Controlled Human Malaria Infection studies in low resource settings: Experiences and perceptions of study participants in a malaria Challenge study in Kenya

Abstract: Background:The range and amount of volunteer infection studies, known as Controlled Human Infection Model (CHMI) studies, in Low-Middle Income Countries (LMICs) is increasing with rapid technological advancement, world-class laboratory facilities and increasing capacity development initiatives. However, the ethical issues these studies present in LMICs have not been empirically studied. We present findings of a descriptive social science study nested within a malaria volunteer infection study, on-going at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 23 publications
4
84
1
Order By: Relevance
“…Some stakeholders felt HIS volunteers should receive higher amounts, in line with suggestions in some guidance [34]. However, other stakeholders were concerned about undue influence, a concern widely shared in literature [2,13,28] and of particular significance in LMIC contexts where poverty may increase the value of study compensation [10]. Existing research in Kenya shows compensation can be a key driver of participation [10], but other studies in Kenya suggest compensation did not involve undue influence, and also did not set a precedentanother concern for some stakeholders in Malawi [8].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Some stakeholders felt HIS volunteers should receive higher amounts, in line with suggestions in some guidance [34]. However, other stakeholders were concerned about undue influence, a concern widely shared in literature [2,13,28] and of particular significance in LMIC contexts where poverty may increase the value of study compensation [10]. Existing research in Kenya shows compensation can be a key driver of participation [10], but other studies in Kenya suggest compensation did not involve undue influence, and also did not set a precedentanother concern for some stakeholders in Malawi [8].…”
Section: Discussionmentioning
confidence: 94%
“…However, other stakeholders were concerned about undue influence, a concern widely shared in literature [2,13,28] and of particular significance in LMIC contexts where poverty may increase the value of study compensation [10]. Existing research in Kenya shows compensation can be a key driver of participation [10], but other studies in Kenya suggest compensation did not involve undue influence, and also did not set a precedentanother concern for some stakeholders in Malawi [8]. While many stakeholders suggested amounts for financial remuneration, some talked about access to health care as a potential form of compensation, reflecting the costs of accessing high quality (private sector) health care in Malawi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent social science work with participants has suggested that HCS participation, particularly in inpatient studies, can lead to a wide range of burdens. 49 Certain study interventions will be more burdensome for some individuals/populations than for others. Due to cultural beliefs regarding the value/importance of blood, for example, blood draws (especially of larger volumes) may be especially worrisome, and thus burdensome, to some research participants in sub-Saharan Africa.…”
Section: Other Burdens For Participantsmentioning
confidence: 99%